PENGARUH KOMITMEN DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN PADA APLIKASI HALODOC DI RUMAH SAKIT ISLAM IBNU SINA PADANG - Sofiah Rilma Nisza (JURNAL PUNDI, 2020)
Fast traslate Icon translate This research is motivated by the phenomenon where a service company must be able to keep its customers loyal so that customers remain subscribed for a long period of time. This study aims to determine the effect of commitment and trust in customer loyalty on Halodoc applications at the Ibnu Sina Islamic Hospital in Padang. The sampling technique uses purposive sampling method. The number of samples used for analysis was 100 respondentsSofiahrilm. The analytical method used is multiple regression analysis, for testing hypotheses using the statistical t test. The results of this study indicate that Commitment has a positive and significant effect on Customer Loyalty in Halodoc Applications at Ibnu Sina Padang Islamic Hospital, trust has a positive and significant effect on Customer Loyalty on Halodoc Applications at Ibnu Sina Padang Islamic Hospital.